The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis

Borderlands: The new mestiza - Anzaldúa, Gloria (Spinsters, Aunt Lute, 1987)
Rooted in Gloria Anzaldúa’s experience as a Chicana, a lesbian, an activist, and a writer, the groundbreaking essays and poems in this volume profoundly challenged how we think about identity. Borderlands/La Frontera remapped our understanding of what a “border” is, seeing it not as a simple divide between here and there, us and them, but as a psychic, social, and cultural terrain that we inhabit, and that inhabits all of us. This twentieth-anniversary edition features new commentaries from prominent activists, artists, and teachers on the legacy of Gloria Anzaldúa’s visionary work
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; féminisme décolonial; identités LGBTQIA2+; lit3220; littérature; mexique; pol4212; premier cycle; queer; régions géographiques; thématiques; états-unis; études littéraires

Passionate politics: Feminist theory in action - essays, 1968-1986 - Bunch, Charlotte (St. Martin's Griffin, 1987)
Essays discuss feminism, reform, lesbianism, education, the media, and the status of women around the world
Keywords: 1900-1999; amériques; approches et analyses; discipline; féminisme radical; hétérosexisme; lesbianisme; militance; mouvements des femmes*; périodes historiques; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; théories féministes; états-unis

Il n'y a pas de cogito-femme - Collin, Françoise (L'émergence d'une culture au féminin, 1987)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; histoire et politique; interdisciplinarité; philosophie; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; thématiques; études culturelles; études littéraires

Méthodologie féministe et anthropologie: une alliance possible - Dagenais, Huguette (Anthropologie et Sociétés, 1987)
Méthodologie féministe et anthropologie : une alliance possible Après un bref énoncé des principes épistémologiques et éthiques qui sous-tendent la recherche féministe et de la stratégie qui en découle dans la poursuite de projets concrets, l'auteure examine les affinités et apports réciproques entre anthropologie et méthodologie féministe puis souligne les contradictions profondes qui, selon elle, rendent problématique actuellement le développement de la recherche féministe en anthropologie. Elle termine en suggérant quelques pistes à suivre par les anthropologues féministes dans un proche avenir.
Keywords: 1900-1999; 1980-1989; amérique du nord; amériques; anthropologie; approches et analyses; cours; discipline; discours dominant; europe; méthodologie; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques

Reading black, reading feminist: A critical anthology - Gates, Henry Louis (Meridian Book, 1987)
A unique and comprehensive collection of 26 literary essays that provides real evidence of the rich cultural history of black women in America. Black women’s writing has finally emerged as one of the most dynamic fields of American literature. Here, leading literary critics—both male and female, black and white—look at fiction, nonfiction, poetry, slave narratives, and autobiographies in a totally new way. In essence, they reconstruct a literary history that documents black women as artists, intellectuals, symbol makers, teachers, and survivors. Important writers whose work and lives are explored include Toni Morrison, Gloria Gaynor, Maya Angelou, and Alice Walker, and the fascinating list of essays range from Nellie Y. McKay’s “The Souls of Black Women Folk in the Writings of W. E. B. Du Bois” to Jewelle L Gomez’s very personal tribute to Lorraine Hansberry as a dramatist and crusader for social justice. Henry Louis Gates Jr., the editor of this anthology and a noted authority on African-American literature, has provided a thought-provoking introduction that celebrates the experience of “reading black, reading feminist.” A penetrating look at women’s writing from a unique perspective, this superb collection brings to light the rich heritage of literary creativity among African-American women.
Keywords: 1900-1999; afro-féminisme; amériques; anthologie; approches et analyses; cours; discipline; fem1000; femmes* noires; féminismes noirs; pratiques féministes; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; états-unis; études littéraires

La recherche-action : ses fonctions, son fondement et son instrumentalisation - Goyette, Gabriel; Lessard-Hébert, Michelle (Presses de l'Université du Québec, 1987)
Cet ouvrage définit la recherche-action et ses grands principes et aborde ses finalités et fonctions. On y trouve des tableaux récapitulatifs des fondements et grandes étapes associées à ce type de recherche. (résumé équipe ORPCC)
Keywords: 1900-1999; 1980-1989; amériques; groupes communautaires; groupes de femmes; orpcc; outils; pour des recherches en milieux de pratiques; périodes historiques; québec; recherche en milieux de pratique; recherche-action; ressource en ligne; régions géographiques

Women, violence and social control - Hanmer, Jalna; Maynard, Mary (Humanities, 1987)
Keywords: amériques; continuum de violences; cours; discipline; europe; royaume-uni; régions géographiques; sciences humaines; sociologie; thématiques; trs3500; violences; violences conjugales; violences contre les femmes*; états-unis

Le Bordel: Milieu De Travail Contrôlé - Lévesque, Andrée (Labour / Le Travail, 1987)
PENDANT LONGTEMPS, des milliers de femmes gagnèrent leur vie dans des bordels à Montréal. L'étude de leur milieu de travail pendant les années vingt et trente révèle une organisation hiérarchique et des conditions dont le contrôle échappait aux principales intéressées. L'appareil judiciaire et policier, les organisations de réformes sociales, le clergé et les médecins hygiénistes affectaient, par la tolérance ou la répression, le cadre dans lequel s'exerçait la prostitution. Plus directement, les souteneurs, les tenancières et leurs gérantes déterminaient les conditions quotidiennes de travail. Les changements observés pendant toute cette période sont plus imputables à la vigilance policière qu'aux fluctuations économiques ou aux efforts des travailleuses elles-mêmes.
Keywords: 1900-1999; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; montréal; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; thématiques; travail; travail du sexe; travail du sexe-prostitution

Des cailloux blancs pour les forêts obscures - Marchessault, Jovette (Collection Roman québécois, 1987)
Qualifié à sa parution en 1987 de « roman du troisième œil » par Gloria F. Orenstein, ce livre raconte un moment dans la vie de Jeanne – depuis sa retraite des Appalaches, au sein d’une petite communauté d’esprits nouveaux –, alors que se meurt sa compagne, Noria. Aviatrice, cette dernière sauve des laboratoires les bêtes torturées à des fins de recherches expérimentales. Sur le seuil de sa vie revient son père, le Lion de Bangor, avec qui elle s’était réconciliée. Ce médecin, qui étudie les cellules souches du cancer, lève enfin pour Jeanne l’écrivaine les derniers voiles sur la vie de Noria : sa naissance, son enfance au sein du Ku Klux Klan, ce fils qu’elle a perdu, et cet amour infini que le Lion lui porte, un amour « comme ces ponts miraculeux sur lesquels nous avançons les uns vers les autres. » « Ce dernier volet de la trilogie Comme une enfant de la terre met en scène Noria, une aviatrice qui, telle une chamane, vole à travers le ciel nocturne de l’Amérique du Nord pour livrer au monde un message de salut et un espoir de guérison, et Jeanne, l’écrivaine qui pratique son propre art magique de la guérison : l’art de la littérature. » — GLORIA F. ORENSTEIN
Keywords: 1900-1999; amériques; approches et analyses; care; histoire et politique; hétérosexisme; littérature québécoise; périodes historiques; racisme; roman; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques; violences

Geography of gender in the third world - Momsen, Janet Henshall; Townsend, Janet G. (University of New York Press, 1987)
This pioneering book addresses a key issue in development studies. It follows the influential 'Geography and Gender' as the second collaborative work generated by the Women in Geography Study Groups of the Institute of British Geographers. Its twenty substantive papers explore spatial patterns of gender in Asia, Africa, the caribbean and Latin America. The book's contributors come from Europe, North and South America, India, Sri Lanka, Malaysia, Thailand, Egypt and the Caribbean. 'Geography of Gender in the Third World' analyses the position of women and the societies that ignore and exploit them. it provides both substantial original research and a comprehensive introduction to the geography of gender in low income countries. The book makes a powerful claim for the regional geography of gender.
Keywords: 1900-1999; afrique; amériques; asie; cours; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; régions géographiques; sud global; thématiques

Les représentations des rapports hommes-femmes dans la chanson populaire au Québec - Nadeau, Sylvie (Université Laval, 1987)
Keywords: 1900-1999; 1980-1989; amériques; culture populaire; mémoires/thèses; périodes historiques; québec; régions géographiques

La création musicale chez les religieuses de trois communautés montréalaises - Rhéaume, Claire (Université de Montréal, 1987)
Keywords: DIG; amériques; arts; discipline; montréal; musique; mémoires/thèses; régions géographiques; soeurs de sainte-anne; soeurs de sainte-croix; soeurs des saints noms de jésus et de marie

Maria W. Stewart, America's first Black woman political writer : essays and speeches - Stewart, Maria W. (Indiana University Press., 1987)
En rassemblant et en présentant les œuvres de Stewart, Richardson offre aux lecteurices l'occasion d'étudier les pensées et les paroles de cette influente militante noire, précurseuse de Frederick Douglass et de Sojourner Truth et première noire américaine à donner des conférences pour la défense des droits des femmes, la plaçant dans le contexte du mouvement abolitionniste tourbillonnant.
Keywords: 1800-1899; afro-féminisme; amériques; antiesclavagisme; approches et analyses; cours; discipline; droits des femmes*; fem1000; femmes* afro-américaines; féminismes noirs; histoire; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis

L'émergence d'une culture au féminin - Zavalloni, Marisa (Collection Femmes, 1987)
Comment définir une culture au féminin ? Quelles formes peut-elle prendre dans les sciences sociales, la littérature, la philosophie et l’art ? Les recherches présentées dans ce recueil, par leur approche analytique, humoristique, caustique, radicale ou poétique, apparaitront comme la poursuite du même idéal, créer une société dans laquelle « les femmes s’appartiennent totalement, non seulement physiquement, mais symboliquement ».
Keywords: 1900-1999; 1980-1989; amériques; cours; droits des femmes*; fem1000; interdisciplinarité; premier cycle; périodes historiques; québec; régions géographiques; thématiques; études culturelles